Conduction velocity in myelinated nerve fibres of Xenopus laevis - Hutchinson, N. A. (1970)
1. The relationship between conduction velocity and nerve diameter in single myelinated nerve fibres from Xenopus laevis was measured and was found to be linear. 2. The relationship between conduction velocity and temperature in nerve fibres of various diameters was measured over the range 15-30° C and was found to be linear for each fibre. 3. The slope of the conduction velocity—temperature relationship was directly proportional to the diameter of the nerve fibre. 4. The form of the conduction velocity—temperature relationship was determined by numerical solution of the Frankenhaeuser—Huxley equations for the case of a propagated action potential. The computation predicted that conduction velocity is a linear function of temperature over the range studied.